Long-term multicenter observational study of the drug Alflutop in Russia: use in patients with knee osteoarthritis (report 4) - E. A. Taskina; L. I. Alekseeva; N. G. Kashevarova; A. M. Lila (Современная ревматология)
Objective: to investigate the efficacy of Alflutop therapy in patients with knee osteoarthritis (OA) with or without concomitant diseases. Material and methods. The large-scale, multicenter prospective, open-label, observational, non-interventional ISKRA study (Study: Prescribing the drug Alflutop, solution for injection, for OA in real world clinical practice) included 22,525 patients, 10,616 of whom had knee OA. The mean age of patients with knee OA was 60.1±11.7 years, body mass index (BMI) was 28±4.6 kg/m2 , and median disease duration was 60 [24; 120] months. All patients had significant comorbidities: arterial hypertension in 90% of cases, and ischemic heart disease, diabetes mellitus and obesity in one in three cases. Alflutop was administered daily 1 ml intramuscularly (IM), No. 20, or every second day 2 ml IM, No. 10. The efficacy of the treatment was assessed by the dynamics of pain intensity using a visual analogue scale (VAS), patient's general health assessment (PHA) using VAS and quality of life using EQ-5D, and the need for non-steroidal anti-inflammatory drugs (NSAIDs). Results and discussion. After one course of treatment, median pain intensity decreased from 60 [40; 70] to 20 [10; 40] mm, quality of life improved – median EQ-5D increased from 0.59 [0.36; 0.69] to 0.85 [0.73; 1]) and PHA from 50 [37; 70] to 80 [60; 90] mm, and the need for NSAIDs decreased. Female gender, older age, high BMI, severe pain, radiological stages III and IV, poorer quality of life, presence of concomitant diseases and lower adherence to treatment were associated with a less significant response to therapy. Conclusion. The results of the use of Alflutop in knee OA suggest that widespread use in real-life clinical practice is possible. The inclusion of additional therapeutic targets in the OA treatment strategy, as well as the identification and correction of factors associated with a less pronounced analgesic effect of the drug, will potentially improve treatment efficacy.